Al-Razi works and contributions in neurological sciences - Abd rahman, Nur Rahilah; Shuriye, Abdi Omar (IIUM Press, 2011)
This chapter investigates AI-Razi's contributions in neurology and the main focus of it is to accrue AI-Razi works in neurological sciences. Related information and data were col1ected from reliable sources. Abu Bakar Muhamed Ibn Zakariya Al-Razi was born in the Iranian city of al-Rayy, south of modern Tehran at 864 AD and came to Baghdad to study medicine and subsequently completed his medical training in Muqtadiri Hospital